Kebijakan Transgenik di Beberapa Negara - Sripratiwi Sripratiwi (JURNAL ILMU KEFARMASIAN INDONESIA, 2005)
The transgenesis as part of biotechnology is expanding tremendously i.e in the pharmaceutical, medical and agricultural field. Thanks to transgenesis the amount and quality of the products for export could be improved. The United States and China for example with cotton and other agricultural products like maize, soy bean and rice. Transgenic research in Indonesia is conducted by Litbang LIPI, Balitbio Agriculture in Bogor, Intercollegiate Center and others, but assessed from the national viewpoint there exist no policy or priority research of transgenesis in Indonesia. It is to be hoped that in the near future in Indonesia such a regulation and policy concerning transgenesis exist, in order to protect the consumer from imported transgenic products.